Development of safety deposit box rental contracts outside the banking sector in Polish business practice - Bączyk, Mirosław (Studia Iuridica Toruniensia, 2024)
The author starts from presenting the rapid development of the so-called safe-deposit box agreements outside the scope of banking transactions and points to the contract terms which regulate that sphere of the market. In the author’s opinion, these agreements are similar to those offered by banks as far as their structure is concerned. The scope of banks’ agreements is still limited, since only banks can and do offer them. In the course of further consideration, the author presents the parties to nonbanking safe-box agreements, the power of attorney granted by the tenant, and analyzes the rights and obligations of the parties to the agreement. It qualifies the agreement as a special lease agreement (Article 659 of the Civil Code). However, he does not exclude the possibility of other qualifications (e.g., as a new, original contractus innominatus). He also discusses the duration of the agreement, remuneration for the landlord, the legal consequences of the tenant’s death, the contractual liability of a non-banking entity, and its obligation to keep professional secrecy. This is the first broader elaboration concerning safe-deposit box agreements outside the scope of banking transactions in Polish literature.